(untitled) (Research, Society and Development, 2022)
Surgically assisted rapid maxillary expansion (SARME) is the main treatment option for transverse maxillary deficiency in adults. This technique depends on the use of expanders, which are commonly related to the movement of teeth in the maxilla, however, there are no studies analyzing the occurrence of alterations in the lower teeth to this date. The aim of this study was to assess the movement of upper and lower teeth produced by SARME executed by means of two surgical techniques with different types of corticotomies on the anterior wall of the maxilla. The sample consisted of 87 cone beam computed tomography (CBCT) scans, which were divided in two groups according to the osteotomy performed: Group I (n = 42) Le Fort I subtotal osteotomy with a step on the zygomatic-buttress and Group 2 (n = 45) Le Fort I type subtotal osteotomy with a linear descending osteotomy of the maxilla. The time periods evaluated were divided into preoperative (T0), immediately after activation of the expander device was ceased (T1) and ending of orthodontic containment period (T2). The data were tabulated and compared between the periods studied and statistically analyzed by means of analysis of variance for repeated measurements (ANOVA) and Tukey’s test for comparison between the three time periods. The total number of individuals (GI + GII) and each isolated group (GI) (GII) were analyzed. The results showed a statistically significant increase of all the maxillary dimensions associated with buccal inclination; mandibular dentoskeletal effects on thewidth of the lingual cortex were observed, there was also an increased distance between the apexes of teeth 46 and 36, and buccal inclination of thetooth 36 were noted, however, only the latter was statistically significant (p <0.05).